A unique complication of radiofrequency therapy to the tongue base. (2015) - Tornari, Chrysostomos; Wong, Gentle; Arora, Asit; Kotecha, Bhik
Highlights: Tongue base radiofrequency ablation may introduce infection to a thyroglossal cyst. This can be managed with antibiotics and ultrasound-guided needle aspiration. Caution is required in radiofrequency therapy for patients with thyroglossal cysts. Abstract: Introduction: Radiofrequency ablation treatment of the tongue base can be used either alone or as part of a multilevel approach in the treatment of snoring. This involves the generation of thermal energy around the circumvallate papillae of the tongue. Potential complications include ulceration, dysphagia, haematoma and abscess formation. Presentation of case: We present the case of a 50-year-old patient who developed an anterior neck swelling following a second application of radiofrequency ablation therapy to the tongue base for snoring. This was secondary to an infection of a previously undiagnosed thyroglossal cyst. The patient made a full recovery following intravenous antibiotic therapy and ultrasound-guided needle aspiration. Discussion: Thyroglossal tract remnants are thought to be present in seven percent of the adult population. An infection in a thyroglossal tract cyst has not previously been reported following radiofrequency ablation of the tongue base. Given the relatively high complication rate of tongue base radiofrequency ablation in some series, this complication may be under-recognised. Conclusion: An infected thyroglossal tract cyst should be suspected in patients with anterior neck swellings following radiofrequency ablation therapy to the tongue base. We advise caution when performing this procedure on patients with known thyroglossal tract remnants though there is insufficient evidence to suggest that this procedure is contraindicated.